Suitability Trials of Different Species and Provenances of Pines in the Doon Valley of India - Ghosh, R. C.; Singh, Bakhshish; Sharma, K. K. (Indian Forester, 1981)
An experiment based on 24 treatments comprising of 9 provenances of Pinus caribaea, 6 provenances of P. patula, 2 provenances of P. kesiya, 3 provenances of P. roxburghii and one each of P. gregii P. pseudotrobus, P.leiophylla and P. glabra was laid out in 1974 at the Forest Research Institute, in a randomized block desigrn with three replications to select suitable species/provenances of pines for afforestation under Dehra Dun conditions. The results of the study at the end of three years growth indicate that P. gregii of Mexico origin is the most suited species. The other species/provenances which have given encouring results are P. petula of Newzealand and Malawi orgins, P. caribaea of Nicargua - Alamicamba, and Guatemala-Deten region and P. kesiya of Thailand. The indigenous chir pine (P. roxburghii) of Debra Dun origin was better (or almost as good in overall performance) than certain provenances of P. caribaea, P. patula, P. kesiya and P. glabra. Intensive provenance trials and selection are indicated in the case of P. gregii, P. caribaea, P. kesiya and P. roxburghii.